Release me! previously unreleased projects - Abellan, Miguel (Instituto Monsa de Ediciones, 2012)
There are some design projects that have never seen the light before, staying in the drawer and failed to be released. In this book, we wanted to pick up this collection of works bringing them to life, under no limits or conditions, designs that have never been produced, published or printed in nay graphic discipline--corporate image, packaging, advertising, and computer graphics.